PARIWISATA RELIGI SEBAGAI PARIWISATA BERKELANJUTAN: PREFERENSI PENUNJANG EKONOMI KERAKYATAN DI KOTA SEMARANG - Hasna Azhaari (UIN Sunan Kalijaga, 2024)
The city of Semarang holds various local wisdom that can be used in tourism activities. The tourism potential in Semarang City that has a sustainability impact can be seen from the strategic location of the city and culture that gives birth to spatial value in the aspect of religiousness being able to play a role in the formation and development of a tourism area. The purpose of this study is to find out the role of religious tourism as sustainable tourism in Semarang City and as one of the supports for the people's economy. Using a qualitative method through a case study approach, taking a field observation process and interviews with the Semarang City Culture and Tourism Office, and important figures in religious tourism management. The results of the study show that religious tourism in Semarang City has the potential to be sustainable tourism even though it cannot become the main tourism as the spearhead of the economy. The increasing number of religious tourists in Semarang City can contribute to the economy and become sustainable tourism from various existing potentials. It is hoped that this research can help the Semarang City Government develop religious tourism to increase the income of the regional economy of Semarang City and the people's economy, by creating so that religious tourism is not left behind and can compete in existing contemporary tourism.